Motivational and psychological variables related to unethical uses of artificial intelligence across multiple life domains (academics and online interactions) - Kyle J. Messick; Ash Bass; Matthew Fulmer; Justine Williams; Jade Anderson; Mattie Wolff; Hope Taylor; Eli Wright; Graceyn Yonce; Blanca Aranda (PLoS ONE, 2026)
Past studies about unethical uses of generative artificial intelligence (AI) have focused within a specific life domain (e.g., how AI is used for cheating in academics). An online survey was conducted to investigate how AI users utilized AI across multiple domains, how unethical behaviors in one domain related to behaviors in others, and which motivational and psychological variables corresponded with those uses. The goal was to help create a foundational understanding of how people use AI more broadly, including what the largest motivations for unethical use are and if unethical use had psychological consequences for the user. Creating this foundation can help develop successful interventions for unethical AI use. Findings supported that performing potentially unethical behaviors in one area of life (e.g., academics) were positively related to unethical behaviors in another area of life (e.g., social media interactions). Using AI unethically was positively related to knowing that the use was unethical. Unethical AI use was not related to intrinsic or extrinsic motivation, but was positively related to results pressure (prioritizing outcomes), external pressure (unethical use is normative and unlikely to be penalized), and time pressure (saving time by completing a task more quickly). Unethical AI use was also positively related to a desire for social media popularity and narcissism. Unethical uses of AI were not related to self-esteem, self-efficacy, or loneliness, but were positively related to satisfaction with life, making social comparisons, internalizing the perspective of others about their own body, prioritizing physical appearance over other attributes, and comparing one’s physical appearance with others. This study provided evidence that despite ethical misuse, generative AI is being used across multiple domains of life and is largely associated with positive consequences for the user. Unethical AI use was applied across multiple areas of life and was associated with variables related to elevating status, achieving good outcomes, behaving within broader cultural norms, and saving time. Future applications could explore if a more wholistic approach that targets motivations is more effective than a domain-specific approach when attempting to create interventions to curb unethical AI use.